Evaluate x → a lim ln ( x 2 − a 2 + 1 ) x 2 − a 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y = x 2 − a 2 . Then as x → a , y → 0 . The limit becomes y → 0 lim ln ( y + 1 ) y . Apply L'Hôpital's rule gives y → 0 lim 1 / ( y + 1 ) 1 = y → 0 lim ( y + 1 ) = 1 .
We can use L'Hopital's Rule here because when we plug a in we get a 0 0 situation: x → a lim ln ( x 2 − a 2 + 1 ) x 2 − a 2 ⟹ x → a lim d x d ( ln ( x 2 − a 2 + 1 ) ) d x d ( x 2 − a 2 ) = x → a lim x 2 − a 2 + 1 2 x 2 x = x → a lim x 2 − a 2 + 1 = a 2 − a 2 + 1 = 1
We have the standard limit :
h → 0 lim ln ( 1 + h ) h = h → 0 lim h ln ( 1 + h ) = 1
Letting x 2 − a 2 = h , we get the required limit as 1 .
"Fakesolve" solution:
Let a = 0 . The limit simplifies to x → 0 lim ln ( x 2 + 1 ) x 2 . Directly substituting x = 0 results in an indeterminate form where we can use L'Hopital's Rule. Then:
x → 0 lim ln ( x 2 + 1 ) x 2 = L. H. x → 0 lim ( x 2 + 1 2 x ) 2 x = x → 0 lim x 2 + 1 = 1
Problem Loading...
Note Loading...
Set Loading...
Let u = x 2 − a 2 . Then by Maclaurin series :
u → 0 lim 1 + u u = u → 0 lim u − 2 u 2 + 3 u 3 − ⋯ u = u → 0 lim 1 − 2 u + 3 u 2 − ⋯ 1 = 1 for ∣ u ∣ < 1 Divide up and down by u